Assessing the Opportunity for an Accelerated Access Pathway for Health Canada Priority Review Drugs: A Comparative Analysis with Ontario’s FAST Pilot Program - Catherine Y. Lau; Arif Mitha; Allison Wills (Current Oncology, 2026)
Background: Timely public reimbursement of innovative medicines remains a challenge in Canada despite expedited regulatory review pathways. This study evaluated whether an accelerated reimbursement pathway, similar to Ontario’s Funding Accelerated for Specific Treatments (FAST) for oncology drugs approved through Project Orbis could improve access for therapies approved through Health Canada’s Priority Review (PR) pathway, extending to indications beyond oncology. Methods: Health Canada drug submissions completed between 2021 and 2025 were reviewed to characterize PR, Notice of Compliance with conditions (NOC/c), and Project Orbis. Drug submissions completed in 2022 were selected for detailed analysis. Drug review and approval process data were compiled from Health Canada (HC), Canada’s Drug Agency (CDA-AMC), the pan-Canadian Pharmaceutical Alliance (pCPA), Ontario government, and manufacturer sources. Time from Health Canada Notice of Compliance (NOC) to Ontario public listing was compared for Orbis, PR non-Orbis, and FAST therapies. Results: Among drugs approved in 2022, mean time from NOC to Ontario listing was 625.29 ± 365.80 days for PR non-Orbis and 604.18 ± 283.92 days for Orbis. FAST therapies were listed in 229.22 ± 140.50 days, approximately 60% faster than Orbis and PR non-Orbis. Half of PR approvals in 2022 were not associated with Project Orbis and were therefore ineligible for existing accelerated reimbursement pathways. Conclusions: The Ontario FAST program is associated with substantially shorter times to public listing for novel oncology medicines. Extending a similar accelerated access pathway to therapies approved through PR could improve timely and equitable patient access in Canada.